2006
DOI: 10.1203/01.pdr.0000196368.08210.5c
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Infection Reversed Anti-Asthma Effect of Neonatal Bacillus Calmette-Guerin Vaccination in BALB/c Mice

Abstract: Bacillus Calmette-Guerin (BCG) vaccination can protect animals from asthma, but the effect of BCG on childhood asthma prevention is controversial in humans. To verify the hypothesis that the BCG anti-asthma effect in childhood might be reversed by a respiratory virus infection, newborn BALB/c mice were divided into five groups. Control and ovalbumin (OVA) groups were mock vaccinated and mock infected. The BCG/OVA group was BCG vaccinated and mock infected. The respiratory syncytial virus (RSV)/ OVA group was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…DNA vaccination may directly target DCs involved in allergen‐specific T H 1‐cell responses, showing preventive effects when delivered at low doses in mice [18,19]. Vaccination with DNA vaccine inhibited the development of airway inflammation [20–22]. Our data demonstrated that DNA vaccine coding OVA allergen directly to DCs was also effective in treating allergen‐induced allergic airway inflammation.…”
Section: Discussionmentioning
confidence: 68%
“…DNA vaccination may directly target DCs involved in allergen‐specific T H 1‐cell responses, showing preventive effects when delivered at low doses in mice [18,19]. Vaccination with DNA vaccine inhibited the development of airway inflammation [20–22]. Our data demonstrated that DNA vaccine coding OVA allergen directly to DCs was also effective in treating allergen‐induced allergic airway inflammation.…”
Section: Discussionmentioning
confidence: 68%
“…Further experiments on neonatal mice have confirmed that when exposed to bacteria inducing Th1 or Treg responses mice were protected from eosinophilic lung inflammation and airway hyperreactivity [64,65]. Thus suggesting the nature of early life infections determines subsequent immune responses and determines either an increased predisposition or protection from the development of allergic airways disease.…”
Section: Early Life Infections and Aberrant Immune Responsesmentioning
confidence: 94%
“…The airway hypersensitivity-responsiveness was measured after exhibition to BCG, and the cells in the washing fluid to bronchialveolar was counted, whose cytokines were detected by ELISA (Li et al, 2006). The control of infection is mediated by M. tuberculosis-specific CD4+ and CD8+ T cells way to the secretion of IFN- and other Th1 cytokines that activate anti-mycobacterial mechanisms of infected macrophages (Shi et al, 2003).…”
Section: T Cells (T Cells Cd4 and T Cells Cd8)mentioning
confidence: 99%